Domestic trade and market size in late eighteenth-century France - Daudin, G (University of Oxford, 2008)
Market size is claimed by various economic traditions to be an important factor in explaining the transition to modern economic growth. This paper examines whether differences in market size might explain the retardation of the Industrial Revolution in France. It uses an exceptional source on French domestic trade in a variety of goods in the late eighteenth century: the Tableaux du Maximum. The first part presents this source and the data. The second part assesses whether the data are plausible using a logit theoretical gravity equation. The third part uses the results of this gravity equation to compute the expected market size of specific supply centres. For all types of high value-to-weight goods, some French supply centres reached 25 million people or more. For all types of textile groups, some French supply centres reached 20 million people or more. Even taking into account differences in real, nominal and disposable income per capita, these supply centres had access to domestic markets that were at least as large as the whole of Britain. Differences in the size of foreign markets were too small to reverse that result.